Impact of ownership and board structure on corporate social responsibility disclosure of listed commercial banks of sri lanka - Mithushana, R.; Johnathan Kevin, S.P.T.; Vijayakumaran, R. (University of Jaffna, 2019)
The purpose of this study is to examine the relationship between corporate social responsibility (CSR) disclosure and ownership and board structure in domestic licensed commercial banks in Sri Lanka. Ownership and board structure have been identified as independent variables and CSR disclosure identified as the dependent variable in this study. The researcher selected 11 high performance domestic licensed commercial banks as a sample for a period of six years starting from 2012 to 2017. Based on the analysis results, there is a significant, positive impact between CSR disclosure and institutional ownership and foreign investors has a significant negative impact on CSR disclosure. Further managerial ownership has insignificant impact on CSR disclosure. Also board structure does not show a significant impact on CSR disclosure in listed licensed commercial banks in Sri Lanka. Researcher concludes that different ownerships have different impacts on the bank’s CSR reporting.
Keywords: Board structure; Commercial banks; Corporate social responsibility; Ownership structure